Existentialism of Main Characters in the Movie: Final Destination 5 - Ni Kadek Wina Valentina; Putu Weddha Savitri; Yana Qomariana (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This study examines the portrayal of existentialist principles and characterization in Final Destination 5 (2011), directed by Steven Quale. The research aims to identify the methods of characterization used for the five main characters and explore how Sartrean existentialism is reflected in their struggles. Using a qualitative approach, the study applies Kenney’s method of characterization and Sartre’s existentialist framework to analyze key scenes, dialogues, and character interactions. Data was collected through repeated viewings of the film, with critical moments transcribed and categorized based on characterization methods and existential principles. The findings reveal that Final Destination 5 employs a mixed method, with the dramatic method being the most dominant, supplemented by character on other characters and contextual methods to develop psychologically complex main characters. Existentialist principles emerge strongly, particularly the idea that "existence precedes essence," as characters are stripped of predefined roles and forced to define themselves through desperate actions. The burden of freedom and responsibility is evident in moral dilemmas, while the confrontation between anguish and authenticity shapes their responses to impending death. Sam’s journey from fear to acceptance exemplifies Sartrean authenticity, whereas Nathan’s ethical crisis highlights the paradox of human freedom.